Overview and early results of the Global Lightning and Sprite Measurements mission. Issue 9 (11th May 2015) - Sato, M.; Ushio, T.; Morimoto, T.; Kikuchi, M.; Kikuchi, H.; Adachi, T.; Suzuki, M.; Yamazaki, A.; Takahashi, Y.; Inan, U.; Linscott, I.; Ishida, R.; et al.
Abstract Global Lightning and Sprite Measurements on Japanese Experiment Module (JEM‐GLIMS) is a space mission to conduct the nadir observations of lightning discharges and transient luminous events (TLEs). The main objectives of this mission are to identify the horizontal distribution of TLEs and to solve the occurrence conditions determining the spatial distribution. JEM‐GLIMS was successfully launched and started continuous nadir observations in 2012. The global distribution of the detected lightning events shows that most of the events occurred over continental regions in the local summer hemisphere. In some events, strong far‐ultraviolet emissions have been simultaneously detected with N2 1P and 2P emissions by the spectrophotometers, which strongly suggest the occurrence of TLEs. Especially, in some of these events, no significant optical emission was measured by the narrowband filter camera, which suggests the occurrence of elves, not sprites. The VLF receiver also succeeded in detecting lightning whistlers, which show clear falling‐tone frequency dispersion. Based on the optical data, the time delay from the detected lightning emission to the whistlers was identified as ∼10 ms, which can be reasonably explained by the wave propagation with the group velocity of whistlers. The VHF interferometer conducted the spaceborne interferometric observations and succeeded in detecting VHF pulses. We observed that the VHF pulses are likely to be excited by the lightning discharge possibly related with in‐cloud discharges and measured with the JEM‐GLIMS optical instruments. Thus, JEM‐GLIMS provides the first full set of optical and electromagnetic data of lightning and TLEs obtained by nadir observations from space.